Analisis Pengaruh Pemanfaatan Media Sosial Instagram Sebagai Media Promosi Online Terhadap Minat Pendaftaran Taruna Baru di STTKD Yogyakarta - Anisa Dwi Apriliani (Jurnal Multidisiplin Madani, 2022)
This study was to Analyze how influential the use of Social Media Instagram is in conducting online promotions on the interest in registering new students at STTKD Yogyakarta. The location of this research is the College of Aerospace Technology, Data used is primary data and using a questionnaire sample used was the new collage students of STTKD Yogyakarta. This research is a quantitative with data analysis method using simple linear regression The results of the calculation analysis show that Instagram social media has a positive effect on buying interest with a significance value of 0.00 (less than of 0.05) and the magnitude of the influence of social media variables on registration interest is 0.820, or 82%.